'It's just a natural human thing to do, to go and visit your family… but it's not easy for us': Gender and generation in Bangladeshis' transnational visits between London and Sylhet. (28th November 2022) - Miah, Md Farid; King, Russell
Abstract: In the title to this paper, Maya, a British‐Bangladeshi woman, expresses her frustration at the refusal of the Home Office to grant her father in Sylhet a visa to come and fulfil his role as family head at the wedding of his son, Maya's brother, in London. The case illustrates well the intersection of gender and generation that fundamentally shapes the pattern of visits, in both directions, across this long‐distance transnational social and family space. Bangladesh is a patriarchal society, with marked gender divisions layered across generations, which are largely reproduced among the migrant community in London and are manifested, in various ways, in the phenomenon of transnational visiting. Based on 61 in‐depth interviews in London and Sylhet, supplemented by participant observation, we delineate the gendered and generational structures framing the visits, both of migrants to the homeland and of non‐migrants to their relatives in London.